PROBLEMATIKA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MADRASAH - Abdul Haris Hasmar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Learning the History of Islamic Culture in Madrasas must be oriented, meaningful, and relevant to the times. Learning does not work well without using methods according to the material being taught. Learning the history of Islamic culture at this time has not been running as it should, as students' perceptions of learning the history of Islamic culture are boring. This study basically examines the problematics of learning the history of Islamic culture in Madrasah Aliyah in Aceh Jaya. The formulation of the problem what problems are faced in learning as well as what steps are taken in overcoming the problem of learning the history of Islamic culture ?. The results showed that students' perceptions of learning the history of Islamic culture were less interesting and could even be said to be boring. In order to improve the persession, there have been several attempts by teachers in the study of the history of Islamic culture in Madrasas. The efforts made by the teacher are 1) improving the learning strategy, the teacher of Islamic cultural history subjects has tried to do creativity, namely using a variety of methods, of course, student-centered; 2) provide motivation to learn every time a meeting; 3) assessing the process at each meeting; 4) using an individual, educational, experience and historical approach.